Developing young athletes: The role of private sport schools in the Norwegian sport system - Kristiansen, E.; Houlihan, B. (International Review for the Sociology of Sport, 2017)
The aim of the paper is to analyse the increasingly prominent role of private sports schools in the development of elite athletes in Norway. The context for the analysis is the apparent paradox between the emergence of a network of sports schools, the most successful of which are private and require that parents pay a fee, and the social democratic values of Norway. Data were collected through a series of interviews with 35 respondents from nine stakeholder groups, including athletes, coaches, parents and sport school managers. The research describes an elite sport system that is successful in producing medal-winning athletes, but which is organisationally fragmented, uncoordinated and under-funded with regard to youth talent identification and development and susceptible to tensions between key actors. The primary analytical framework is Kingdon`s multiple streams framework augmented by path dependency theory. The findings include, a picture of an elite youth sport development system in which multiple and overlapping problems have received, at best, only partial policy solutions some of which, such as the growth of private sports schools, have emerged by default. When focusing attention on the relationship between structure and agency in the policy process it is argued that the government, through its inaction, has allowed sports schools the policy space to expand. The consequence is that the government has, whether deliberately or not, enabled the strengthening of a commercial elite youth sport development system, while still preserving its egalitarian and non-interventionist credentials.